2004
DOI: 10.1126/science.1098119
|View full text |Cite
|
Sign up to set email alerts
|

Ultraconserved Elements in the Human Genome

Abstract: There are 481 segments longer than 200 bp that are absolutely conserved (100% identity with no insertions or deletions) between orthologous regions of the human, rat and mouse genomes. Nearly all of these segments are also conserved in the chicken and dog genomes, with an average of 95% and 99% identity, respectively. Many are also significantly conserved in fish. These ultraconserved elements of the human genome are most often located either overlapping exons in genes involved in RNA processing or in introns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

63
1,607
8
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,570 publications
(1,714 citation statements)
references
References 36 publications
63
1,607
8
13
Order By: Relevance
“…Interestingly NFAT5 exon 5 is one of the 111 'ultraconserved elements' identified in human protein-coding genes (Bejerano et al, 2004;McGlincy and Smith, 2008). It has been reported that many ultraconserved elements are associated with exons inducing NMD ( (Bejerano et al, 2004;McGlincy and Smith, 2008). In this context, the ddx5/ddx17 effect on NFAT5 expression was observed in different human cell lines (Figure 4) as well as in a mouse cell line (Supplementary Figure S4).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly NFAT5 exon 5 is one of the 111 'ultraconserved elements' identified in human protein-coding genes (Bejerano et al, 2004;McGlincy and Smith, 2008). It has been reported that many ultraconserved elements are associated with exons inducing NMD ( (Bejerano et al, 2004;McGlincy and Smith, 2008). In this context, the ddx5/ddx17 effect on NFAT5 expression was observed in different human cell lines (Figure 4) as well as in a mouse cell line (Supplementary Figure S4).…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, ddx5 and ddx17 favored the inclusion of the NFAT5 exon 5, which generated unproductive transcripts that were not translated ( Figure 6). Interestingly NFAT5 exon 5 is one of the 111 'ultraconserved elements' identified in human protein-coding genes (Bejerano et al, 2004;McGlincy and Smith, 2008). It has been reported that many ultraconserved elements are associated with exons inducing NMD ( (Bejerano et al, 2004;McGlincy and Smith, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…42 detected regions are contained within one of the different cDNA collections. 38 overlap with one of the 481 "ultraconserved elements" (segments longer than 200 base pairs that are identical between human, mouse and rat genomes) reported by Bejerano et al 30 . A few of these can be unambiguously identified as structural RNAs because of the substitution pattern in the fish and chicken sequences.…”
Section: Structures Conserved Across All Vertebratesmentioning
confidence: 82%
“…The existence of transcriptionally highly active genes also in the gene-poor environment of the nuclear periphery argues for an impact of other factors such as the switching of replication timing, ultra-conserved DNA elements (Bejerano et al 2004), and local chromatin unfolding in addition to the influence of local gene density. Finally, the observation of gene-dense chromatin confirmed in a variety of different cell types and species so far does not implicate that such an arrangement is mandatory and does not exclude the existence of specific cell types with an opposite nuclear distribution.…”
Section: Discussionmentioning
confidence: 99%